A qualitative inquiry on the effects of COVID-19 pandemic on hospitality industry in Malaysia / Nur Hidayah Che Ahmat ... [et al.] - Che Ahmat, Nur Hidayah; Wan Ismail, Wan Rusni; Ramli, Rafidah Aida; Rahamat, Syafiqah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
The COVID-19 pandemic grievously hit the Malaysian hospitality industry; hence, the government implemented various restriction orders and preventative measures, which impacted business operations. This paper describes the challenges hospitality managers face during the early phase of COVID-19 in Malaysia and examines the effects of the COVID-19 pandemic on the attractiveness of hospitality jobs and occupations. The researchers interviewed 13 managers from hotels and restaurants via phone interview method. Using qualitative data analysis suggested by Creswell (2013), the researchers found five main challenges: controlling costs, overseeing sales and revenues, surviving competition, managing the workforce, and prioritising human safety and health. Findings suggest that the COVID-19 outbreak has influenced hospitality job attractiveness. The industry is still recovering from the impact and facing difficulties in recruiting talent. Nonetheless, COVID-19 has accelerated the usage of technology in the hospitality industry. Many companies have invested in technology innovations such as contactless payment, QR codes for check-in and check-out customers, and food delivery robots. Since the interviews were conducted during the early phase of the pandemic, future research could investigate the current phenomenon in the post-COVID, considering many businesses have operated albeit with labour shortages. Additionally, future research could investigate employees to gather their perspectives regarding hospitality jobs and occupational attractiveness.